THERAPEUTIC COMMUNICATION FOR PEOPLE WITH HIV (ODHIV) THROUGH SPIRITUAL CONSULAR IN CARLO ROOM, ST. CAROLUS HOSPITAL JAKARTA AND NON SPIRITUAL IN INDONESIA POSITIVE NETWORK (JIP) - Nur Desilawati (Jurusan Ilmu Komunkasi FISIP Universitas Jenderal Soedirman, 2025)
Indonesia ranks fifth as the country with the highest HIV/AIDS-related death rates in the world, with 27,000 deaths in 2023. The cumulative number of people living with HIV/AIDS from 2005 to 2023 is 566,707. In 2023 alone, the number of people with HIV/AIDS reached 57,299, the highest figure since 2009. This situation is certainly concerning. Therefore, preventive efforts, treatment, and care are needed to ensure that people living with HIV (PLHIV) remain healthy. More broadly, it is hoped that the death rate due to HIV/AIDS does not rise and that the transmission does not spread further. Various preventive, treatment, and care efforts are being carried out by different parties, including NGOs and healthcare facilities (Faskes). In Indonesia, NGOs focusing on these efforts include Jaringan Indonesia Positif (JIP), and healthcare facilities that are quite focused on PLHIV include the Unit Ruang Carlo at St. Carolus Hospital in Jakarta. However, the care or counseling provided varies. In the Ruang Carlo, there is the involvement of doctors, nurses, and counselors, such as the Suster-suster Cinta Kasih St. Carolus Borromeus, while at JIP, there is only the involvement of counselors who are experts in their field, having undergone specialized counseling training and education. The treatment provided at the Ruang Carlo is referred to as holistic care or counseling, while JIP implements palliative care or counseling. The similarity between the two types of care or counseling is the role of the counselor, who performs therapeutic communication with people living with HIV (PLHIV). Therefore, this research focuses on the counselor's experience in conducting therapeutic communication, which includes the motivations behind the counseling activities, the communication experiences themselves, and the types of messages exchanged, both verbal and non-verbal.